V13 [videorecording (DVD)] - Didier-Weill, Alain; Ledes, Richard; Cumming, Alan, 1965-; Levine, Samual H.; Aiken, Liam (Deskpop Entertainment, 2025)
Vienna, 1913, Europe is on the brink of WWI. Two young men become friends: Hugo, a musician from a privileged family, tries psychoanalysis with Sigmund Freud. Adolf, a struggling artist, obsessed with vegetarianism, falls in love with German Nationalism.